The Effect Of Nigella Sativa Oil On Induced Hypothyroidism In White Mice - فاضل هيام كامل; حسن حلا ياسين (Latakia University Journal -Biological Sciences Series, 2021)
This study aimed to determine The effect of Nigella sativa oil seeds on levels of FT3,FT4,TSH in the blood serum of White adult mice of induced hypothyroidism and evaluates it’s therapeutic influence. This study included 30 female white mice ( Balb/c strain ) which were divided into three experimental group .10 mice in each .the first group was the physiological control treated orally with 0,9% Nacl until the end of the experiment. the second group was the pathological control treated orally with methimazole in dose of (0,05mg/kg) for three weeks and the third group was treatment group treated orally with 1ml/kg of Nigella Sativa oil for 4 weeks .at the end of experiment e blood simples were collected for biochemical analysis. Result showed that the oil of nigella sativa seeds has positive effect on hypothyroidism since the level of FT3, FT4 were significantly increase (p<0.05) ,moreover significantly decreas (p<0.05) in level TSH was recorded.